2018
DOI: 10.2151/jmsj.2018-033
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Himawari-8/AHI Radiometric Calibration Based on Two Years of In-Orbit Data

Abstract: The new geostationary (GEO) meteorological satellite of the Japan Meteorological Agency (JMA), Himawari-8, entered operation on 7 July 2015. Himawari-8 features the new 16-band Advanced Himawari Imager (AHI), whose spatial resolution and observation frequency are improved over those of its predecessor MTSAT-series satellites. These improvements will bring about unprecedented levels of performance in nowcasting services and short-range weather forecasting systems. In view of the essential nature of navigation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…1 and 2 originated from stray light. The results of our research show that those effects exert definite influence upon the nighttime images of the 1.6-µm and 2.3-µm bands over very long periods during each yearabout 6 months, as suggested by Okuyama et al (2018). Examples of the stray light that affects the AHI images are shown in Fig.…”
Section: Possible Causes For Pseudo-thermal Anomalysupporting
confidence: 68%
See 2 more Smart Citations
“…1 and 2 originated from stray light. The results of our research show that those effects exert definite influence upon the nighttime images of the 1.6-µm and 2.3-µm bands over very long periods during each yearabout 6 months, as suggested by Okuyama et al (2018). Examples of the stray light that affects the AHI images are shown in Fig.…”
Section: Possible Causes For Pseudo-thermal Anomalysupporting
confidence: 68%
“…The most useful clue for the cause of the anomaly is the timing of its appearance. The fact that the pseudo-thermal anomaly appears in the vernal and autumn equinox periods suggests that it is closely related to earth eclipse (Okuyama et al 2018), that is, when a geostationary satellite, such as Himawari-8, enters the shadow of the earth (Fig. 3a).…”
Section: Possible Causes For Pseudo-thermal Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…The radiometric accuracies of the MTSAT-2 Imager and Himawari-8/AHI have been validated using high spectral resolution sounders such as the Atmospheric Infrared Sounder (AIRS) onboard the Aqua satellite [23] or the Infrared Atmospheric Sounder Interferometer (IASI) onboard the MetOp satellite [24] through the Global Space-based Inter-Calibration System (GSICS) [25]. As for the MTSAT-2 Imager, Hewison et al showed that the IR channels (IR1 at 10.8 µm, and IR2 at 12 µm) had stable biases with the averages of +0.08 K for IR1 and +0.10 K for IR2 for two years from June 2010 [25], while Okuyama et al mentioned that the biases of some IR channels (e.g., IR2) tended to increase to 1.5 K at nighttime around the eclipse season, whereas those seen during the daytime were a tenth of these values [26]. As for Himawari-8/AHI, Okuyama et al showed that the IR bands (bands 7 to 16) were calibrated within 0.2 K with no significant diurnal variation [26].…”
Section: Overviewmentioning
confidence: 99%
“…As for the MTSAT-2 Imager, Hewison et al showed that the IR channels (IR1 at 10.8 µm, and IR2 at 12 µm) had stable biases with the averages of +0.08 K for IR1 and +0.10 K for IR2 for two years from June 2010 [25], while Okuyama et al mentioned that the biases of some IR channels (e.g., IR2) tended to increase to 1.5 K at nighttime around the eclipse season, whereas those seen during the daytime were a tenth of these values [26]. As for Himawari-8/AHI, Okuyama et al showed that the IR bands (bands 7 to 16) were calibrated within 0.2 K with no significant diurnal variation [26].…”
Section: Overviewmentioning
confidence: 99%